Waiting times and treatment following cancer diagnosis: comparison between immigrants and the Norwegian host population. (2nd April 2020) - Thøgersen, Håvard; Møller, Bjørn; Åsli, Linn Merete; Bhargava, Sameer; Kvåle, Rune; Fjellbirkeland, Lars; Robsahm, Trude Eid; Aaserud, Stein; Babigumira, Ronnie; Larsen, Inger Kristin
Abstract: Background: There are concerns about timely access to appropriate cancer treatment for the growing immigrant population in Norway. This study aims to compare waiting times between cancer diagnosis and start of cancer treatment, as well as treatment patterns between immigrants in Norway and the host population. Material and methods: We performed a nationwide, registry-based study with individual-level data, including 213, 320 Norwegians and 8324 immigrants diagnosed with breast, colorectal, lung or prostate cancer in 1990–2014. Differences in time from diagnosis to treatment and in treatment patterns were described for the selected cancer sites. The Cox and logistic regressions were used to adjust for patient and tumour characteristics. Results: After adjustment for covariates, hazard ratios for time from diagnosis to treatment for non-Western immigrants compared to Norwegians were 0.88 (95% confidence interval (CI): 0.82–0.95) for breast cancer and 0.84 (95% CI: 0.75–0.95) for lung cancer, indicating longer waiting times. Treatment patterns in the four major cancer sites were similar among immigrants and the Norwegian host population, except for breast cancer, where women from East and South Asia received less breast-conserving surgery than the Norwegian host population (adjusted odds ratios 0.65 (95% CI: 0.46–0.93) for East Asians and 0.75 (95% CI: 0.50–1.13) for South Asians). Conclusions: The present study reports delayed treatment for lung and breast cancer among immigrants from non-Western countries in Norway. Systematic differences in cancer treatment were not detected. However, less breast-conserving surgery among breast cancer patients from Asia compared to Norwegians was observed.